Edukasi Pentingnya Administrasi Bagi Pengelola Keuangan Daerah Provinsi Sumatera Selatan - Edwar juliartha; Suandi Suandi; Firdaus Fakih; Yuslainiwati Yuslainiwati; Arie Firmansyah (Jurnal Pengabdian Pasca Unisti (JURDIANPASTI), 2025)
The purpose of this service is to educate the importance of administration for Regional Financial Managers. Administration is the main foundation that forms the structure and function of a company. The administrative role is not only limited to routine office tasks, but also has a significant impact on the overall success of the company. One of them is financial administration which is at the core of the success of a company or institution